The quest for tolerant varieties: the importance of integrating “omics” techniques to phenotyping - Zivy, Michel; Wienkoop, Stefanie; Renaut, Jenny; Pinheiro, Carla; Goulas, Estelle; Carpentier, Sebastien (Frontiers in Plant Science, 2015)
The primary objective of crop breeding is to improve yield and/or harvest quality while minimizing inputs. Global climate change and the increase in world population are significant challenges for agriculture and call for further improvements to crops and the development of new tools for research. Significant progress has been made in the molecular and genetic analysis of model plants. However, is science generating false expectations? Are ‘omic techniques generating valuable information that can be translated into the field? The exploration of crop biodiversity and the correlation of cellular responses to stress tolerance at the plant level is currently a challenge. This viewpoint reviews concisely the problems one encounters when working on a crop and provides an outline of possible workflows when initiating cellular phenotyping via “-omic” techniques (transcriptomics, proteomics, metabolomics).